Shot trajectory parameters in gold medal stationary shot-putters during world-class competition - Frossard, L.; Smeathers, J.; Goodman, S. (Adapted Physical Activity Quarterly, 2007)
The parameters of the shot`s trajectory were reported for male and female gold medalists (classes F52, F53, F54, and F55) who competed at the 2000 Paralympic Games and the 2002 International Paralympic Committee (IPC) World Championships. The specific objective was to determine the magnitude of differences in these parameters across classes and genders. The release velocity of the shot increased with the performance and the classification for both males (8.30 m/s-9.96 m/s) and females (4.58 m/s-8.50 m/s). The measured angle of the shot`s trajectory at release also increased with the performance and the classification for both males (27.54¡-32.47¡) and females (9.02¡- 34.52¡). The position of the shot from a fixed reference point at release revealed a similar trend for both males (2.01 m-2.68 m) and females (1.16 m-1.98 m), although it was weaker.